Local pottery, hybrid identities: Exploring the Zapo-Teotihuacáno community at El Tesoro, Hidalgo through ceramic compositional analysis. (October 2022) - Pierce, Daniel E.; Holt Mehta, Haley; Ferguson, Jeffrey R.
Highlights: The site of El Tesoro in Hidalgo, Mexico features numerous traits connecting the site to both Teotihuacan and the Valley of Oaxaca. NAA analysis of ceramics at El Tesoro indicates local likely production of ceramics even when exhibiting foreign styles. Though more than one paste recipe has been identified at the site, the same recipe was used to create both Teotihuacan and Zapotec style ceramics. Given the mixture of cultures exhibited in both ceramics and burials, we believe this represents a creolized culture, rather than a colony. This type of cultural hybridization supports a trade diaspora model in which individuals relocate to frontier areas for the purposes of facilitating trade between disparate locales. Abstract: Understanding cultural identity has been a critical aspect of archaeology since its inception. The Bordes-Binford debate famously tackled the issue of cultural identity based upon material culture in the 1960 s. Since then, the issue of cultural affiliation has been addressed in a variety of ways. Critical to this is the understanding of colonization, diasporas, and immigration. In this study, we consider the topic of cultural identity at the site of El Tesoro, Hidalgo, which exhibits cultural elements related to both Teotihuacán and the Valley of Oaxaca. Given the presence of both cultural styles, El Tesoro has previously been suspected to be a Zapotec enclave, perhaps founded by people who emigrated from the Oaxaca Barrio of Teotihuacán. One important example of the dual cultural representations is in the ceramic assemblage at El Tesoro. In this study, we have used Neutron Activation Analysis to assess provenance for a number of sherds which feature distinct Zapotec or Teotihuacán styles. Our results indicate that these ceramics were not the product of importation, but they were presumably made locally, even using the same recipes across both cultural traditions. Given these results and other mixed cultural expressions such as burials, we suggest that this indicates hybridization between the two cultures. Rather than affiliating themselves with one culture or the other, we propose that the Classic period community at El Tesoro can more accurately be described as "Zapo-Teotihuacáno", as a creolization of both cultures. In contrast with a colonization or enclave model, El Tesoro may instead be thought of as the product of a trade diaspora in which individuals/groups moved to frontier locations as a way to facilitate trade between disparate locales. In doing so, they were incentivized to take on traits of both cultures.